Dynamic assessment of the impact of gut microbiota transfer in a mouse model of chronic intestinal dysbiosis. (28th May 2021) - Orci, L; Lacotte, S; Gex, Q; Lazarevic, V; Schrenzel, J; Toso, C
Abstract: Objective: There is growing evidence supporting that the gut microbiota is a major driver of human health and disease. While gut microbiota transfer (GMT) is commonly used as an approach to restore "eubiosis", there is a surprising lack of data on whether the transferred microbiota efficiently and durably repopulate the gut of the transplanted subject. Moreover, little is known on the effects of GMT on non-alcoholic fatty liver disease (NAFLD). Methods: Chronic dysbiosis and NAFLD-like liver injury were induced by feeding C57Bl/6j mice for 16 weeks with a high-fat diet. For GMT, dysbiotic mice underwent preliminary gut cleansing, followed by oral gavage with a suspension of fresh fecal matter procured from a pool of lean mice (1 dose, or 10 doses). We next characterized microbiota composition and we measured the relative abundance of specific pathobionts in recipient mice, using high-throughput shotgun analysis in a dynamic manner, over time. All experiments took place in a specific germ-free environment. Results: After 4 months on a high-fat diet, mice displayed fatty liver infiltration with moderate parenchymal inflammatory changes. Dysbiosis was evidenced by a reduced bacterial diversity, as well as a dramatically increased abundance of Firmicutes, and lower Verrucomicrobia and Actinobacteria. Gut microbiota transfer was associated with a transitory reduction in NAFLD-induced hepatocellular injury. While dysbiotic mice displayed a shift in their microbiota composition towards that of lean donors after GMT, this effect rapidly faded after one week, and mice recovered their initial, dysbiotic microbiota. Conclusion: The current study indicates that, when used in mice with chronically established dysbiosis, GMT is merely associated with transitory changes in gut microbiota composition, as well as significant but moderate reduction in hepatocellular injury.